The elderly have similar outcomes compared to younger patients after ORIF with locking plate for comminuted proximal humerus fracture - Tzu-Cheng Yang; Yu-Ping Su; Ming-Chau Chang (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to compare clinical and radiological outcomes of elder and younger patients with comminuted proximal humerus fracture treated with osteosynthesis with locking plate. Methods: A total of 70 patients (30 males and 40 females; mean age 65.4 years) operated on for Neer 3- or 4-part proximal humeral fractures between 2010 and 2016 and followed for at least one-year were included in the study. The reduction was achieved through intraosseous window to minimize soft tissue stripping in all patients and structural allograft at metaphyseal diaphyseal junction was used aggressively to resist varus force. Group 1 consisted of 32 patients aged 70 or older (14 males and 18 females; mean age: 77.8 ± 5.1), while Group 2 consisted of 38 patients younger than 70 (16 males and 22 females; mean age: 58.2 ± 9.3). The groups were compared for their clinical and radiological outcomes. Results: There was no significant difference in clinical outcomes by Oxford score (54.8 ± 2.7 vs 56.6 ± 3.4, p = 0.13) and ASES score (89.7 ± 5.7 vs 90.8 ± 8.2, p = 0.68). Two groups had similar radiological outcomes regarding neck shaft angle, greater tip height and offset. However, group 2 had better final shoulder forward elevation (162.6 ± 8.7 vs 135.4 ± 14.7ß, p < 0.05) and shorter duration to achieve maximal range of motion (4.37 ± 2.37 vs 8.14 ± 3.25 months, p < 0.05) than group 1. Two groups had similar complication rates (9.4% vs 7.9%). All the complications were related to greater tuberosity including mal-reduction and avulsion. Conclusion: With the prerequisite of good alignment with robust medial cortical support and untouched soft tissue over medial metaphysis area via intra-osseous reduction, comminution of proximal humeral fracture can achieve satisfactory result and low complication rate by osteosynthesis with locking plate system, regardless of age. In addition, we suggested to use structural bone graft for comminuted medial cortex fracture with multiple fragments or bony defect more than 2 cm. Level of evidence: Level III Therapeutic study. Keywords: Elderly, Complications, Locking plate, Osteosynthesis, Proximal humerus fracture